2018
DOI: 10.22146/ijc.26785
|View full text |Cite
|
Sign up to set email alerts
|

Density-Functional-Theory Calculations of Formation Energy of the Nitrogen-Doped Diamond

Abstract: The geometry optimization of the nitrogen-doped diamond has been carried out by the density functional theory (DFT) calculations. We model the defective diamond of substitutional and interstitial nitrogen atoms by using a simple-cubic supercell. Atoms in the supercell are relaxed by allowing them to move so that the atomic forces are less than 5.0 × 10-3 eV/Å. We calculate the formation energy for substitutional and interstitial sites. We find that the formation energy for the substitutional defect is10.89 eV.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 23 publications
0
11
0
Order By: Relevance
“…In each supercell, one dopant atom was located at a substitutional lattice site in the outer layers. While B [53] and N [54,55] atoms are known from previous studies to favour substitutional sites, it is not clear whether this is also the case for O atoms. IR absorption spectra of O-containing DLC films often indicate the presence of carbonyl oxygens [20] (C=O), but other studies found O incorporation in bridge positions (two C-O bonds) to be more stable [46], or have suggested the presence of epoxy groups [6,50].…”
Section: Methodsmentioning
confidence: 97%
“…In each supercell, one dopant atom was located at a substitutional lattice site in the outer layers. While B [53] and N [54,55] atoms are known from previous studies to favour substitutional sites, it is not clear whether this is also the case for O atoms. IR absorption spectra of O-containing DLC films often indicate the presence of carbonyl oxygens [20] (C=O), but other studies found O incorporation in bridge positions (two C-O bonds) to be more stable [46], or have suggested the presence of epoxy groups [6,50].…”
Section: Methodsmentioning
confidence: 97%
“…Moreover, the defect volume is calculated before modification/pure diamond (𝑉 0 ) and after modification by carbon-vacancy-hydrogen (𝑉 𝑓 ). The volume changes before and after relaxation (∆𝑉) is calculated by the following equation [34]: We also calculate the formation energies for each defect structure by using equations as follows [26]:…”
Section: Methodsmentioning
confidence: 99%
“…We then calculate the formation energy Eform and charge transfer. The Eform is defined by using the following equation [27][28][29][30][31]:…”
Section: ■ Computational Methodsmentioning
confidence: 99%